Contemporary computing for engineers and scientists using Fortran 90 - Forsythe, Chester (Boston : PWS, 1997)
This book is about: An intuitive walk through the world of computers; Learn to design first; Subroutines; ...
Keywords: Computer program language; FORTRAN 90.; FORTRAN 90 (Computer program language)